Exploring Pre-Service Teachers' Readiness to Embrace Digital Literacy Skills in English Instructional Settings - Oktaviani Oktaviani; Khairunnisa Khairunnisa (UMBanjarmasin, 2022)
This study examines the implementation of digital literacy skills by pre-service teachers in English language classes in the context of the fourth industrial revolution (IR 4.0). Through qualitative methods including interviews and Likert scale questionnaires, data was collected from 24 pre-service teachers at UIN Antasari Banjarmasin. The findings reveal that pre-service teachers actively utilize digital technology in their classrooms and prioritize credible sources for teaching materials. However, they face challenges related to limited network access, inadequate facilities, and students' limited digital technology knowledge. The study highlights the importance of integrating media technology in class to foster student interest in learning, while emphasizing that it is a teaching technique rather than a crucial factor. It concludes that even without media technology, classes can still be effectively conducted. These insights contribute to understanding the digital literacy skills of pre-service teachers and the implications for English language instruction.